(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article discusses the regeneration of cardiomyocytes and highlights recent advances in cardiomyocyte regeneration, focusing on the molecular mechanisms underlying myocardial repair and the translation of these findings into potential therapeutic applications. Particular attention is given to stem cell–based therapies, cellular reprogramming, gene editing technologies, and bioengineering approaches that aim to restore cardiac function following injury.